Mechanical properties of trabeculae and osteocyte morphology change significantly in different areas of the necrotic femoral head - He, Min-Cong; Tian, Jia-Qing; He, Xiao-Ming; Yang, Peng; Lin, Tian-Ye; Zhang, Qing-Wen; He, Wei; Wei, Qiu-Shi (Frontiers in Cell and Developmental Biology, 2023)
Background: Osteonecrosis of the femoral head is a complex hip ailment. The precise changes in bone tissue during the disease’s onset remain unclear. It is vital to assess both the quantity and quality of the trabecular state in a necrotic femoral head. Aim: This study aims to identify and compare the ultrastructural changes in osteocyte morphology and nanomechanical characteristics within various regions of necrotic femoral heads. Methods: Between December 2016 and May 2023, we gathered ten necrotic femoral heads from patients and five femoral heads from cadavers. The samples from the necrotic femoral heads were categorized into three areas: necrotic, sclerotic, and normal. Our assessment methods encompassed hematoxylin and eosin staining, sclerostin (SOST) immunohistochemistry, micro-computed tomography, nanoindentation, and acid-etched scanning electron microscopy. These techniques enabled us to examine the SOST expression, trabecular microstructure, micromechanical properties of trabeculae, and modifications in osteocyte morphology at the ultrastructural level. Results: The protein level of SOST was found to be lower in the sclerotic area. In the necrotic area, decreased values of bone volume fraction, trabecular thickness, and trabecular number and an increased value of trabecular separation were found. Conversely, in the sclerotic area, higher mean values of bone volume fraction, trabecular number, and trabecular thickness and lower trabecular separation indicated significant changes in the structural characteristics of trabeculae. Compared with the healthy area, the elastic modulus and hardness in the sclerotic area were significantly higher than those in the necrotic, normal, and control areas, while those in necrotic areas were significantly lower than those in the healthy area. The number of osteocytes tended to increase in the sclerotic area with more canalicular cells compared to the healthy area and control group. Conclusion: These results imply that the stress distribution within the sclerotic area could potentially lead to enhanced trabecular quality and quantity. This effect is also reflected in the increased count of osteocytes and their canaliculars. It is plausible that the sclerotic trabecular bone plays a pivotal role in the repair of necrotic femoral heads.